1999
DOI: 10.1159/000022837
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B 5’-Ins/Del and 3’-VNTR Polymorphisms in Chinese, Malay and Indian Singaporeans

Abstract: The allele frequencies for the apolipoprotein B (apo B) 5′-Ins/Del and 3′-VNTR polymorphisms varied significantly (p < 0.01) among Singaporeans of Chinese, Malay and Indian descent. We calculated the unbiased expected heterozygosities for the 5′-Ins/Del polymorphism as 0.3357, 0.1984 and 0.2418, and for the 3′-VNTR as 0.5980, 0.5260 and 0.6749, respectively, in the Chinese, Malays and Indians. Compared to heterozygosities reported for other populations, the Singaporeans differed from most Caucasians in having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…This highly polymorphic locus is located approximately 0.5 kb on the 39-side of the last amino acid codon in the APOB gene (2,3). This highly polymorphic locus is located approximately 0.5 kb on the 39-side of the last amino acid codon in the APOB gene (2,3).…”
Section: Introductionmentioning
confidence: 98%
“…This highly polymorphic locus is located approximately 0.5 kb on the 39-side of the last amino acid codon in the APOB gene (2,3). This highly polymorphic locus is located approximately 0.5 kb on the 39-side of the last amino acid codon in the APOB gene (2,3).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies demonstrated that Asian populations have allele 34 at the highest frequency, whereas allele 36 is most common among Indo-European speaking populations [5,8,9] . Both Bashkir and Komi populations from the south Ural had ap- proximately equal frequencies of alleles 34 and 36, and this is in line with anthropological evidence of an Asian admixture among these ethnic groups [29] .…”
Section: Resultsmentioning
confidence: 99%
“…The 3 ApoB structure shows tandemly repeated sequences that are 14-16 nu-cleotide pairs long and rich in A and T; alleles usually differ from each other by 30 nucleotide pairs or by two repeats [4] . Allele frequencies of this locus vary between populations and have been widely used in investigations of the population history and diversity of humans [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Hopefully, new nutritional and genetic developments will offer opportunities in the near future to develop strategies to target the intestine in order to enhance fat absorption in congenital malabsorptions on the one hand, and reduce postprandial lipemia and prevent atherosclerosis on the other hand. Numerous polymorphisms of the Apo B gene have been described with an effect of the insertion (ins)/deletion (del) polymorphisms on lipid levels (257)(258)(259), and the kinetics of the secretion of VLDLs has already been found ( 260 ). It is noteworthy that the XbaI polymorphism was related to the inter-individual variability observed during postprandial lipemia, showing a signifi cantly augmented or reduced postprandial response ( 261,262 ).…”
Section: Discussionmentioning
confidence: 99%